Work Productivity Based on Work Ability, Compensation, and Work Dicipline - Sudarijati; Harini, Sri; Sari, Vanny Wulan (International Journal of Integrative Sciences, 2024)
Teacher work productivity is one of the crucial factors in improving the quality of education. It helps students to gain the necessary academic progress and personal development. The purpose of this study is to reveal the effect of work ability, compensation, and work discipline on teacher work productivity at Phatnawitya Yala School, Thailand. This study used a quantitative approach with multiple linear regression analysis method. The research sample was 65 teachers of the school. The results showed that simultaneously work ability, compensation, and work discipline have a positive and significant effect on work productivity. Partially, work ability have a positive and significant effect on work productivity, compensation have a positive and significant effect on work productivity, and work discipline have a positive and significant effect on work productivity.